ANALISIS KELAYAKAN FINANSIAL DAN SENSITIVITAS INVESTASI PADA USAHA KIOS DIMSUM’S AND NGEMILS DENGAN MODAL TERBATAS - Aruna, Muhammad Mahitala; Al Kindi, Ali Hamka; Fadhil, Muhammad Quraish; Kusuma, Damar Jaya (Taksasila Edukasi Insani, 2025)
This study analyzes the financial feasibility and investment sensitivity of the micro culinary business “Dimsum and Ngemils,” planned with an initial capital of IDR 10,000,000. Using a financial feasibility approach, the analysis includes funding estimation, cash flow projection, break-even point (BEP) calculation, cost of capital, investment evaluation through NPV, IRR, and Payback Period, as well as sensitivity analysis of key variables. The results show that with a simple capital structure sourced mainly from personal funds and limited external financing, the business is financially feasible and capable of returning the initial investment within approximately five to six months. The positive NPV and IRR of 26% indicate good profitability potential. However, sensitivity analysis demonstrates that the business is vulnerable to fluctuations in raw material prices and sales levels, which significantly affect net profit. Therefore, efficient cost control, accurate cash flow management, and periodic product innovation are essential strategies to maintain financial stability. This study provides practical recommendations for micro and small culinary entrepreneurs to improve financial management, strengthen data-based investment planning, and enhance the long-term sustainability of their businesses. Keywords :business feasibility study, cash flow, BEP, cost of capital, MSMEs, sensitivity analysis